Efficacy Test of Tetanus Leaf (Leea aequata L.) Ethanol Extract against Bacteria (Pseudomonas aeruginosa) - Lumban Gaol, Irma Yohana; Bangar, Roy Indrianto; Kaban, Vera Estefania; Br Sembiring, Novitaria; Harahap, Daimah Wirdatus Sanaun (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Antibiotic-resistant nosocomial infections are caused by the opportunistic bacterium Pseudomonas aeruginosa. The purpose of this study is to use the disc diffusion method to assess the antibacterial efficacy of Tetanus (Leea aequata L.) leaf ethanol extract against Pseudomonas aeruginosa. The antibacterial activity was evaluated at 25%, 50%, and 75% concentrations after the leaves were extracted by maceration with 96% ethanol. The findings indicated that the antibacterial activity was depending on concentration, with respective minimum inhibition level measuring 12.97 mm, 16.7 mm, and 21.06 mm. The negative control (DMSO) displayed no inhibition zone, but the positive control (gentamicin) displayed KHM measuring 25.03 mm. The data distribution did not differ significantly, according to statistical analysis (p > 0.05). Bioactive substances that can harm bacterial cell structures, including flavonoids, alkaloids, tannins, and saponins, were thought to be responsible for this antibacterial action. According to these results, tetanus leaf extract may be used as a natural antibacterial agent and as a substitute for antibiotics in the treatment of Pseudomonas aeruginosa infections